In China's Backyard : Policies and Politics of Chinese Resource Investments in Southeast Asia. - Morris-Jung, Jason (ISEAS - Yusof Ishak Institute, 2017)
""In this fascinating multi-disciplinary and multi-sited volume, the authors challenge reductionist and oversimplifying approaches to understanding China's engagement with Southeast Asia. Productively viewing these interactions through a "resource lens", the editor has transcended disciplinary and area studies divides in order to assemble a dynamic and diverse group of scholars with extensive experience across Southeast Asia and in China, all while bringing together perspectives from resource economics, policy analysis, international relations, human geography, political ecology, history, soci